Weimar on the Pacific : German Exile Culture in Los Angeles and the Crisis of Modernism - Bahr, Ehrhard (Book collections on Project MUSE., 2007)
In the 1930s and '40s, LA became a cultural sanctuary for a distinguished group of German artists and intellectuals - including Thomas Mann, Theodor W. Adorno, Bertolt Brecht, Fritz Lang, and Arnold Schoenberg - who were fleeing Nazi Germany. This book is the first to examine their work and lives.